Effects of enzyme supplementation on growth performance, digestibility of phosphorus, femur parameters and fecal microbiota in growing pigs fed different types of diets - Yin, Yi; Jlali, Maamer; Yu, Bing; Luo, Yuheng; He, Jun; Zheng, Ping; Mao, Xiangbing; Yan, Hui; Wu, Aimin; Bai, Shiping; Devillard, Estelle; Yu, Jie (Frontiers in Veterinary Science, 2024)
A 42-days study was conducted to evaluate the effects of different dietary types (corn-or wheat-soybean meal-based diet) and phytase (Phy) or a multi-carbohydrase and phytase complex (MCPC) supplementation on growth performance, digestibility of phosphorus (P), intestinal transporter gene expression, plasma indexes, bone parameters, and fecal microbiota in growing pigs. Seventy-two barrows (average initial body weight of 24.70 ± 0.09 kg) with a 2 × 3 factorial arrangement of treatments and main effects of diet type (corn-or wheat-soybean meal-based-diets) and enzyme supplementation (without, with Phy or with MCPC). Each group was designed with 6 replicate pens. The MCPC increased (p < 0.05) average daily gain (ADG) and final body weight (BW). A significant interaction (p = 0.01) was observed between diet type and enzyme supplementation on apparent total tract digestibility (ATTD) of P. The ATTD of P was higher (p < 0.05) in wheat soybean meal-based diets compared to corn-soybean meal-based diets. Compared with the corn-soybean meal-based diet, the relative expression of SLC34A2 and VDR genes in the ileum and SLC34A3 in jejunum of growing pigs fed the wheat-soybean meal based diet was lower (p < 0.05). The MCPC significantly reduced (p < 0.05) the relative expression of TRPV5 and CALB1 genes in the ileum and increased the expression of CALB1 in the duodenum compared to control diet. The phytase increased (p < 0.05) the relative expression of SLC34A1 gene in the duodenum in comparison to control diet and MCPC-supplemented diet. The Ca and P contents in plasma from pigs fed corn-soybean meal-based diet were higher (p < 0.05) than those from pigs fed wheat-soybean meal-based diet, and the parathyroid hormone (PTH) and calcitonin (CT) concentrations were lower (p < 0.05) than those fed wheat-soybean meal-based diet. The content of Ca and P in the femur and the bone strength of pigs in the corn-soybean meal group were significantly higher (p < 0.05) than those in the wheat-soybean meal groups. The phytase increased (p < 0.05) the Ca and P content and bone strength of the femur. Additionally, diet type and both enzymes significantly improved fecal microbial diversity and composition. Taken together, diet type and exogenous enzymes supplementation could differently influence the growth performance, utilization of phosphorus, intestinal transporter gene expression, bone mineralization and microbial diversity and composition in growing pigs.